Pengaruh Marketing Mix 4P terhadap Keputusan Pembelian pada Makaroni Ngehe di Daerah Istimewa Yogyakarta - Adawiyah, Hanifah; Rinaldi (CV. Kurnia Grup, 2025)
Along with the fluctuations in the development of the food and beverage industry in Indonesia from 2011, there is one business that still exists from 2013-2024, namely the Makaroni Ngehe snack food. This research aims to analyze the influence of the Marketing Mix (4P) consisting of: Product, Price, Place, and Promotion on Purchasing Decisions for Makaroni Ngehe in the Special Region of Yogyakarta. The type of research used is quantitative research. Random sampling technique (incidental sampling). The research sample consisted of 100 respondents who were Makaroni Ngehe customers in the Special Region of Yogyakarta. Data collection was carried out through distributing questionnaires and data processing was carried out using SPSS 25. Data analysis included data quality testing, classical assumption testing, multiple linear regression testing, and hypothesis testing. The research results show that product, price and promotion have a positive and significant influence on purchasing decisions, while the place variable does not have a significant influence.